Osteopenia and osteoporosis in people living with HIV: multiprofessional approach - Lima AL (Dove Medical Press, 2011)
Ana Lucia Lei Munhoz Lima, Priscila Rosalba D de Oliveira, Perola Grimberg Plapler, Flora Maria D Andrea Marcolino, Eduardo de Souza Meirelles, André Sugawara, Riccardo Gomes Gobbi, Alexandre Leme Godoy dos Santos , Gilberto Luis CamanhoInstitute of Orthopedics and Traumatology, Hospital das Clínicas, University of São Paulo School of Medicine, São Paulo, BrazilAbstract: Increasing bone mineralization abnormalities observed among people living with HIV (PLWHIV) result from various factors relating to the host, the virus, and the antiretrovirals used. Today, HIV infection is considered to be a risk factor for bone mineralization disorders. The test most recommended for diagnosing osteoporosis is measurement of bone mineral density by means of dual energy X-ray absorptiometry at two sites. Osteoporosis treatment has the aims of bone mass improvement and fracture control. A combination of calcium and vitamin D supplementation may reduce the risk of fractures. Antiresorptive drugs act by blocking osteoclastic activity and reducing bone remodeling. On the other hand, bone-forming drugs stimulate osteoblastogenesis, thereby stimulating the formation of bone matrix. Mixed-action medications are those that are capable of both stimulating bone formation and inhibiting reabsorption. Antiresorptive drugs form the group of medications with the greatest quantity of scientific evidence confirming their efficacy in osteoporosis treatment. Physical activity is a health promotion strategy for the general population, but only preliminary data on its real value and benefit among PLWHIV are available, especially in relation to osteoporosis.Keywords: osteoporosis, HIV/AIDS, diagnosis, treatment, exercise